Rancang Bangun Aplikasi Penilaian Kinerja Guru Berbasis Website Menggunakan Metode Graphic Rating Scale ( Studi Kasus : SMA Barunawati Surabaya ) - KUSDIANTORO, ARIF; Sagirani, Tri; Lemantara, Julianto (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2020)
Barunawati High School Surabaya is a high school located at Jalan Perak Barat Number 173 Perak Utara Pabean Cantian District, East Java 60165 Surabaya City under the Barunawati Biru Foundation. At the Barunawati High School in Surabaya the teacher performance appraisal process is still subjective because the teacher performance appraisal is only assessed by the principal directly by considering the assessment criteria. Teacher performance appraisal has not referred to Permendiknas No. 16/2007 concerning standards of academic qualifications and teacher competencies. Teacher performance appraisal does not yet have an assessment history that impacts the difficulty of school principals to see teacher development so far. In addition, the results of the calculation of teacher performance are still many errors because it is done manually. The solution to be made is, a web-based application that can simplify the teacher performance evaluation process. The teacher performance appraisal process will use the Graphic Rating Scale method and refer to the Ministry of Education Regulation No. 16 of 2007 on the standards of academic qualifications and teacher competency. In this Graphic Rating Scale method the performance appraisal will be assessed by the principal's principal, the teacher as himself. The trial results show that this application can provide calculations in accordance with the Graphic rating scale method. And can conduct assessments in accordance with the rules set by No. 16 of 2007 concerning the standards of academic qualifications and teacher competencies. In addition, the application can also provide a historical assessment of teacher performance.